Asymmetric Construction of Halogenated Cyclic Quaternary Carbon Center through Enolate Activation of Aldehydes - Li, Qing-Zhu; Liu, Yue; Leng, Hai-Jun; Li, Jun-Long (Synlett, 2018)
The construction of a chiral halogenated cyclic quaternary carbon center through various catalytic strategies is an emerging hot topic in the field of asymmetric synthesis. Herein, we give a summary of recently developed synthetic methods for preparing such structures. In addition, a novel enolate activation mode of aldehydes is highlighted, which provides an elegant pathway to access enantiopure heterocycles featuring a halogenated quaternary stereocenter through organocatalytic [4+2] cycloaddition.
Keywords: enolate activation; halogenated aldehydes; organocatalysis; quaternary stereocenter; spirocyclopropane